Longitudinal optic neuritis-unrelated visual evoked potential changes in NMO spectrum disorders - Ringelstein, Marius; Jarius, Sven; Wildemann, Brigitte (Neurology, 2020)
Pain is frequent in multiple sclerosis (MS) and includes different types, with neuropathic pain (NP) being most closely related to MS pathology. However, prevalence estimates vary largely, and causal relationships between pain and biopsychosocial factors in MS are largely unknown. Longitudinal studies might help to clarify the prevalence and determinants of pain in MS. To this end, we analyzed data from 410 patients with newly diagnosed clinically isolated syndrome or relapsing-remitting MS participating in the prospective multicenter German National MS Cohort Study (NationMS) at baseline and after 4 years. Pain was assessed by self-report using the PainDETECT Questionnaire. Neuropsychiatric assessment included tests for fatigue, depression, and cognition. In addition, sociodemographic and clinical data were obtained. Prevalence of pain of any type was 40% and 36% at baseline and after 4 years, respectively, whereas prevalence of NP was 2% and 5%. Pain of any type and NP were both strongly linked to fatigue, depression, and disability. This link was even stronger after 4 years than at baseline. Moreover, changes in pain, depression, and fatigue were highly correlated without any of these symptoms preceding the others. Taken together, pain of any type seems to be much more frequent than NP in early nonprogressive MS. Moreover, the close relationship between pain, fatigue, and depression in MS should be considered for treatment decisions and future research on a possible common pathophysiology.
First published December 3, 2019
Gesehen am 24.06.2020